Análise de transferência de energia em vidro fluorogermanato codopado com tb3+ e sm3+ - Pereira, Neudes Ferreira (2019)
Recently, many works have been devoted to the study of the optical and spectral (emission and excitation) properties of optical materials codoped with rare earth ions, for the development of luminescent devices. In particular, the energy transfer process has attained a major role in optical electronics and photonics due to its vast applications in lasers, waveguides, optical fiber amplifiers, solid-state light emitting diodes etc. In this work, we investigate the energy transfer process between Tb3+ and Sm3+ ions, codoped in fluorogermanate glasses, as their concentration is varied. In a qualitative way, we use the energy level diagram as an initial tool to optimize the analysis of the energy transfer process between the ions, when excited at 376 and 483 nm. Further, we investigate in a quantitative way the energy transfer from the superposition of Sm3+ absorption and Tb3+ emission spectra according to the Dexter model and the non-exponential luminescence decay profile adjusted by the parameters of the Inokuti-Hirayama model. The obtained results varying rare earth ion concentrations and excitation wavelength confirm the existence of energy transfer between Tb3+ and Sm3+ and describe the mechanisms behind such process.